2006
DOI: 10.1111/j.1365-294x.2006.03086.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the endangered Cathaya argyrophylla (Pinaceae) inferred from sequence variation of mitochondrial and nuclear DNA

Abstract: Cathaya argyrophylla is an endangered conifer restricted to subtropical mountains of China. To study phylogeographical pattern and demographic history of C. argyrophylla, species-wide genetic variation was investigated using sequences of maternally inherited mtDNA and biparentally inherited nuclear DNA. Of 15 populations sampled from all four distinct regions, only three mitotypes were detected at two loci, without single region having a mixed composition (G(ST) = 1). Average nucleotide diversity (theta(ws) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 72 publications
(143 reference statements)
6
96
6
Order By: Relevance
“…The low genetic diversity within populations and high genetic differentiation among populations we observed in A. ziyuanensis are similar to that of another relictual endangered conifer species in China, Cathaya argyrophylla (Wang et al 1996;Ge et al 1998), which may be partially ascribed to the evolutionary history (Wang and Ge 2006). Specifically, the present distribution of A. ziyuanensis is restricted to several isolated alpine habitats with cold microclimates in South China (Ning et al 2005, Zhang et al 2004).…”
Section: Genetic Structuresupporting
confidence: 69%
“…The low genetic diversity within populations and high genetic differentiation among populations we observed in A. ziyuanensis are similar to that of another relictual endangered conifer species in China, Cathaya argyrophylla (Wang et al 1996;Ge et al 1998), which may be partially ascribed to the evolutionary history (Wang and Ge 2006). Specifically, the present distribution of A. ziyuanensis is restricted to several isolated alpine habitats with cold microclimates in South China (Ning et al 2005, Zhang et al 2004).…”
Section: Genetic Structuresupporting
confidence: 69%
“…However, the level of nucleotide diversity revealed in our study was in the same order or slightly higher than those reported for other conifers e.g., Cryptomeria japonica (π sil = 0.0039) over seven loci (Kado et al, 2003), Cathaya argyrophylla (π sil = 0.0024) (Wang and Song, 2006), Pinus tabuliformis, P. yunnanensis and P. densata (π sil = 0.0087 ~ 0.0128 over 7 loci, (Ma et al, 2006). It thus appears that contrary to previous suggestions Larix species have levels of nucleotide diversity comparable to other conifers.…”
Section: Discussioncontrasting
confidence: 41%
“…This region has been presumed to be a long-term refuge for plant species in general because of its high diversity and endemism (Ying et al 1993;Wu and Wu 1996;Ying 2001;Wang et al 2009). Many ancient plant species, such as Cathaya argyrophylla, Emmenopterys henryi, C. japonicum, Tetracentron sinense, Ginkgo biloba, Thuja sutchuenensis and Metasequoia glyptostroboides, are found in this region (Ying et al 1993;Wang and Ge 2006;Gong et al 2008). Rather unexpectedly in this study, haplotype H13 grouped in the same lineage as H1 (HPGI) but was distributed outside of the Wuling Mts.…”
Section: Potential Glacial Refugiamentioning
confidence: 59%